Childhood and adulthood socioeconomic position and the hospital-based incidence of hip fractures after 13 years of follow-up: the role of health behaviours. Issue 11 (4th February 2011) - van Lenthe, Frank J; Avendano, M; van Beeck, E F; Mackenbach, Johan P
Abstract : Background: To investigate the association between childhood and adulthood socioeconomic position and the hospital-based incidence of hip fractures, and the contribution of health behaviours to these socioeconomic disparities. Methods: Baseline (1991) information about socioeconomic position in childhood and adulthood, behavioural factors (alcohol consumption, smoking, physical inactivity, coffee consumption) and body height of 25–74-year-old participants (n=18 810) were linked to hospital admissions for hip fractures (ICD9 code 820–821) over a follow-up period of almost 13 years. Results: During follow-up 192 hip fractures resulted in hospital admission. Childhood socioeconomic position was not associated with the incidence of hip fractures. Adjusted for body height, a lower educational level and being in a lower income proxy group were associated with an increased probability of hip fractures (HR=1.88, 95% CI 1.00 to 3.53 in the lowest education group; HR=2.39, 95% 1.46 to 3.92 in the lowest income group). Very excessive alcohol consumption, smoking and physical inactivity were associated with an increased probability of hip fractures, and contributed (10–31%) to socioeconomic disparities in hip fractures. Conclusions: The higher prevalence of unhealthy behaviour in lower socioeconomic groups in adulthood contributes moderately to socioeconomic disparities in incidence of hip fractures later in life.